Design of Friction Dampers for Mistuned Bladed Disks - Panning, Lars; Sextro, Walter; Popp, Karl (PAMM)
Friction damping devices such as underplatform dampers are widely used in turbomachinery applications to reduce blade vibration amplitudes. In this paper, a model is presented briefly to calculate the forced response of mistuned bladed systems with friction dampers. Some results will give an insight in the vibrational behavior of frictionally damped bladed disks and how the damping gain is affected by the damper properties.